Mrs. NN”, Correspondent of St. Theophan - Marina I. Shcherbakova (Два века русской классики, 2021)
The article presents materials about Varvara Alexandrovna Iordan, a correspondent and spiritual daughter of St. Theophan, whose letters to her have been printed for over a century as “Letters to Mrs. NN.” Concealment of true names of St. Theophan’s correspondents was often dictated by the addressees themselves, who removed recognizable facts and details when preparing letters for publication. The name of “Mrs. NN” is defined by the mention of this person in a letter to V. V. Shvidkovskaya. By family ties V. A. Iordan (nee Pushchina) was connected with the family of the rector of St. Petersburg University P. A. Pletnev, thanks to whom she met her future husband, the famous engraver F. I. Iordan. The atmosphere of family happiness contributed to the successful work of Iordan on the second engraved portrait of N. V. Gogol, which is confirmed by previously unpublished letters from F. I. Iordan to F. V. Chizhov. Correspondence between V.A. Iordan and St. Theophan began in 1879, four years before the death of her husband. The surviving letters contain information on external events in the life of V.A. Jordan, her spiritual growth under the influence of St. Theophan; his recommendations and advice, assessments and judgments are invaluable. The letters contain many unique testimonies of how the life of the Vysha hermit proceeded in recent years.